Hospital Support for Siblings of Children With Illness in Japan - Niinomi, Kazuteru; Mihira, Hajime; Ochiai, Ryota; Misawa, Akiko; Takigawa, Kuniyoshi; Kashiki, Nagako; Kakee, Naoko; Takata, Hidemi; Ishida, Yasushi; Higaki, Takashi (Frontiers in Pediatrics, 2022)
Recent years have seen increased attention to the needs and support of siblings of children with chronic illness, and reports of intervention studies on siblings are gradually increasing worldwide. In Japan, the basic policy approved by the Cabinet in 2021 of The Basic Law for Child and Maternal Health and Development stipulates promoting support for the siblings of children with chronic illness, medical care, and disabilities. Simultaneously, practical reports are emerging. However, reports on the actual state of sibling support at medical institutions in Japan are limited. This study aimed to describe the actual state of support for siblings of children with illness in Japanese medical institutions using a cross-sectional design. Responses were obtained from 207 of 484 registered training facilities for Board-Certified Pediatricians of the Japan Pediatric Society through anonymous questionnaires investigating the actual state of siblings’ support. Descriptive statistics were calculated, and the state of siblings’ support was described. Fifty-two participants (25.1%) answered that the entire ward, including two outpatient departments, provided siblings’ support, while 37 (17.9%) answered some staff made an effort, and 117 (56.5%) did not. Support mentioned included conversing with siblings, actively speaking to siblings, calling siblings’ names, and counseling care through the parents. Of the 45 cases (21.7%) where siblings were invited to events and gatherings, 10 (22.2%) were siblings-centered events. Some cases involved collaboration with local sibling support groups such as non-profit organizations. This study clarified the actual state of siblings’ support, and further expansion of this support is required.